(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction:. Dyslipidemia is a well known and major modifiable risk factor for coronary heart disease (CHD). Increased prevalence of these abnormalities in young adulthood, increase the prevalence of CHD later on life. Objectives: to estimate the prevalence and patterns of serum lipid profiles and associated factors among university students in Fayoum University students. Methods: A descriptive cross-sectional study was conducted on a group of 384 Fayoum university students. Fasting blood samples were collected from all participants and assayed for fasting total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL), and low density lipoprotein (LDL). Results: According to the National Cholesterol Education Program-Adult Treatment Panel III criteria, the overall prevalence of dyslipidemia was 44.3% , hypercholesterolemia prevalence was 38.8%, hypertrigyceridemia 29.7% low HDL-C 27.1% and high LDL-C 33.1% Significant associated factors of dyslipidemia among study participants were urban residence, increasing age, physical inactivity ,overweight&obesity, abdominal obesity frequent fast food consumption and Low fruit and vegetables consumption Conclusion: The prevalence of dyslipidemia is high among Fayoum university students, important associated factors are obesity and overweight, physical inactivity , unhealthy dietary habits that need to be tackled through intervention programs.